Learning the Practice from the Practice: Theory–Practice Courses in Teacher Education - Orit Oved; Nirit Raichel (Education Sciences, 2024)
In teacher education programs, it is important to deepen knowledge alongside developing practices through practical experience. One practice of the Professional Development School’s (PDS) model in clinical experience is designing courses linking theory to practice. The present study examines the perception of the administrative officers in colleges of education in Israel regarding the Ministry of Education’s Theory–Practice (TP) courses and the challenges in implementing them in the curriculum. This study was conducted in 16 state academic colleges for education and 37 administrative personnel participated: presidents, vice presidents, rectors, deans, and heads of courses and practical training. A semi-structured interview was used, and the data was analyzed thematically. The research participants believe that TP courses as a tool implemented as part of the PDS model may be effective in training teachers to integrate theory with practical experience. The participants raised three major challenges to implementation: systemic, pedagogical, and organizational. The participants emphasize that designing and implementing TP courses is a complex, slow process requiring organizational change and the mindset of administration and teaching staff at both the colleges of education and the schools. Long-term assessment is required to examine the effect of reducing hours dedicated to education theory and subject knowledge.